Silver Showdown - Sharpe, Jon (Sharpe, Jon. Renegade rifles., 2009)
"When Fargo hits the little desert town of Las Vegas, he knows that the nearby silver strikes are filling the town with opportunities of every shape, size, and price. But when he signs on with an old frontier buddy to guard shipments from the mines to the town, he gets pulled into a fight not just against bandits, but against a vendetta-packing family out to end the Trailsman's lucky streak for good."--Page 4 of cover.